Characterization of the pollution process of sediments of the Apodi-Mossoró River in the urban stretch of Mossoró-RN - Bezerra, Joel Medeiros; Batista, Rafael Oliveira; da Silva, Paulo Cesar Moura (Sociedade & Natureza, 2018)
Due to the constant presence of pollutants in the water bodies and the difficulty of understanding information regarding the condition of the river sediments, the characterization of its quality becomes essential. In this way, the objective was to characterize and identify the determinants of the pollution process of the sediments of the Apodi-Mossoró riverbed in the urban stretch of Mossoró-RN. Thirty samples were collected along the course of the Apodi-Mossoró River, within the urban-rural stretch of the municipality of Mossoró. The results of the analysis of the total concentration of the following heavymetals: aluminum (Al), cadmium (Cd), copper (Cu), chromium (Cr), lead (Pb), iron (Fe), manganese (Mn), nickel And zinc (Zn). We applied the multivariate statistical methods of Hierarchical Group Analysis (AAH) and Principal Component Analysis/Factor Analysis (ACP/AF). The distribution of the concentrations of the geochemical parameters in the sediments of the Apodi-Mossoró River were strongly influenced by the characteristics of the collection sites and antropocity. The sampled points were grouped into 4 representative groups regarding the sampling characteristics, identifying possible sites with alterations caused by the anthropic action.